Parental active tracking measures and health behaviors during high school and college. Issue 2 (17th February 2021) - Abar, Caitlin C.; Farnett, Sarah; Mendola, Kayla; Sarra, Sharon; Clark, Gabrielle
Abstract: Objective: This study developed and tested new measures of youth perceptions of parental active efforts to track their activities during adolescence and college. Participants and Methods: Between March and October 2016, a sample of 314 college students aged 18–25 completed a survey including their perceptions of their parent's active tracking efforts during high school and college. Items were then analyzed, and internally consistent measures were derived. Results: The new measures demonstrated significant convergent validity with the three sources of parental knowledge constructs (parental solicitation, parental control, and youth disclosure). Greater perceived parental active tracking efforts during adolescence and in college were associated with better health behaviors in both time periods. Conclusions: The newly derived measures represent appropriate and predictive indices of parental tracking behaviors during adolescence and college, designed specifically with these populations in mind, to be used in pre-intervention and intervention work with parents.